2004
DOI: 10.1111/j.1365-2133.2004.06112.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in infants in their first year of life

Abstract: Although tinea capitis is rare in infants in their first year of life, the condition should be investigated if scaling and/or alopecia are present. A thorough epidemiological study of other family members is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
2
26
0
6
Order By: Relevance
“…Case of TC were more usual in children younger than 10 years of age, as also found in the vast majority of other studies, with TC being the most common cutaneous fungal infection in children aged 3–7 years, 6,12,13,20–22 but rare in adults 2,13 . The incidence of TC in children younger than 1 year of age old is low, with fewer than 100 cases reported, 2,4,7,11,22,24 20 of these in Spain 4,12,18 . In the present study, we found five cases in children younger than 1 year of age, which thus represents the third largest series of these particular cases in Spain, after the 10 cases reported by Gilaberte et al.…”
Section: Discussionsupporting
confidence: 85%
“…Case of TC were more usual in children younger than 10 years of age, as also found in the vast majority of other studies, with TC being the most common cutaneous fungal infection in children aged 3–7 years, 6,12,13,20–22 but rare in adults 2,13 . The incidence of TC in children younger than 1 year of age old is low, with fewer than 100 cases reported, 2,4,7,11,22,24 20 of these in Spain 4,12,18 . In the present study, we found five cases in children younger than 1 year of age, which thus represents the third largest series of these particular cases in Spain, after the 10 cases reported by Gilaberte et al.…”
Section: Discussionsupporting
confidence: 85%
“…In other reports, tinea capitis is a typical dermatological problem in patients between 3 and 7 years of age. It is rarely diagnosed in children under 2 years of age [11,12]. The results of studies conducted in the Unit of Medical Mycology at the Department of Dermatology, Poznan University of Medical Sciences in the years 2013-2016 confirm that the most common period of mycosis is the age between 3 and 7 years.…”
Section: Grzyby Pleśniowementioning
confidence: 52%
“…Według innych doniesień tinea capitis jest typowym schorzeniem dermatologicznym u pacjentów w wieku od 3 do 7 lat. Jest natomiast rzadko rozpoznawana u dzieci poniżej 2 lat [11,12]. Wyniki badań przeprowadzonych w Pracowni Mikologii Lekarskiej w Poznaniu w latach 2013-2016 potwierdzają, że grzybica najczęściej występuje w wieku od 3 do 7 lat.…”
Section: Omówienieunclassified
“…Tinea kapitisin sık görüldüğü, kalabalık, düşük sosyokültürel düzeyli bölgelerde, yaşı 3 aydan büyük, saçında deskuamasyon görülen tüm çocuklarda akla T. kapitis gelmelidir 7 . Bebeklerde en sık rastlanan bulgu yama tarzında alopesi, ardından da ince deskuamasyondur 18 . Tunus'ta yapılan bir çalışma, 2 yaşından önce en sık rastlanan dermatomikozun %46,8'le T. kapitis olduğunu bildirmiştir.…”
Section: Klinikunclassified